Problems of genesis of Slavic statehood in theoretical concepts of legal Slavistics - Melnikov1, Victor Yu.; Seregin, Andrei V.; Marina A. Cherkasova, Igor A. Sizko; Tsechoyev, Valery K. (Opción, 2020)
The article analyzes the problem of the political opposition of Norman, Turanian Gothic and Sarmatian theory-the doctrine of the autochthonous Slavic way of Genesis of medieval Slavic statehood via the method of legal qualification, i.e. verification of the existence of specific dynasties of such features of the state as people, power, territory, rights, etc. As a result, the British came to India for the purpose of colonization and began to call themselves some Chinese or Cambodian ethnonym. In conclusion, the emergence of medieval Slavic statehood is associated with the political creativity of the Slavic peoples.